2018
DOI: 10.1051/e3sconf/20183402033
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of kitchen wastewater using Eichhornia crassipes

Abstract: Abstract. The efficiency of Eichhornia crassipes for treatment of raw kitchen wastewater was studied in the present research work. An artificial wetland of 30 liter capacity was created for phytoremediation of kitchen wastewater using Eichhornia crassipes. Kitchen wastewater samples were collected from hostel of an educational institute in India. Samples were characterized based on physical and chemical parameters such as pH, turbidity, total hardness, nitrate-nitrogen, ammonium-nitrogen, sulphate, dissolved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, a reduction of 26% for TDS was reported by Moyo et al [26] during the treatment of polluted river water using EC. Similarly, Parwin and Paul [13] observed 67.72% and 69.97% reduction in TDS in control and EC, respectively. KWW especially from educational, professional organizations and restaurants is rich in oil and grease.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…However, a reduction of 26% for TDS was reported by Moyo et al [26] during the treatment of polluted river water using EC. Similarly, Parwin and Paul [13] observed 67.72% and 69.97% reduction in TDS in control and EC, respectively. KWW especially from educational, professional organizations and restaurants is rich in oil and grease.…”
Section: Resultsmentioning
confidence: 67%
“…2, TOC showed a good reduction of 38.81% for EC 1 and 39.68% for EC 2 , whereas 35.31% for control in 21 days. In a study conducted by Parwin and Paul [13] after 8 days of the retention time, the removal efficiency of TOC was 15.38% and 13.67% for EC and control, respectively. Rezania et al [15] found a 45% reduction of TOC in 12 days of the experiment.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For treatment system efficiency, the percentage removal efficiency (%) of the pilot-scale treatment system was calculated for each of the wastewater parameters based on the mass flow difference between the effluent and influent relative to the influent [ 68 ]. where Ci = concentration of waste material in influent and Ce = concentration of waste material in effluent.…”
Section: Methodsmentioning
confidence: 99%